PENGARUH DAYA HAMBAT PERASAN BAWANG PUTIH TUNGGAL (Allium Sativum L) TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi - Sofyanita, Eko Naning (poltekkes kemenkes pontianak, 2023)
Typhoid fever is a disease caused by Salmonella typhi bacterial infection. This disease is one of the global infections throughout where the level of typhoid resistance to chloramphenicol in Indonesia itself is increasing, and it has even been reported that resistance increases 16% to 81% in 1 year in one location. Single garlic contains an active compound, namely allicin, which is used as an antibacterial which can inhibit the growth of gram-positive and gram-negative bacteria. Therefore, single garlic is expected to be used as an alternative in overcoming the problem of resistance to bacteria Salmonella typhi that causes typoid. This study used the disc diffusion method on MHA agar media to test the inhibition of single garlic juice against Salmonella typhi bacteria. This type of experimental research with descriptive criteria, with 4 repetitions. Results by measuring the diameter of the power area of the test sample in the concentration group of 50%, 75% and 100%. The results of this study the average diameter of the inhibitory power at a concentration of 100% is 25 mm, at a concentration of 75% is 21 mm, and at a concentration of 50 % i.e. 17 mm. The results of statistical tests with simple linear regression showed that p (0.000) <Î± 0.05 means that Ha is accepted, so it can be stated that there is an effect of various concentrations of single garlic (Allium Sativum L) on the inhibition zone of Salmonella typhi bacteria.